Avaliação radiográfica das iatrogenias ocorridas durante a realização de tratamentos endodônticos por alunos de graduação - Silva, Patricia Zambon da (2016)
The aim of this study was to determine by periapical radiographs, the frequency of iatrogenesis during the mechanical preparation of the endodontic treatments, performed by undergraduate students of the School of Dentistry of UFES, in the Endodontia II discipline, from 2012 to 2014. Radiographic records from 397 endodontically treated single-rooted or double-rooted teeth were randomly selected and analyzed by three examiners, specialized in Endodontics, using the projection of radiographic images. The iatrogenesis evaluation were perforation (root, apex and furcation), strip perforations, presence of fractured instruments, ledges and zips. The root canal preparations were then classified, according to the absence or presence of iatrogenesis, as adequate or inadequate, respectively. The chi-squared test was applied for the comparison among percentages. The 5% level was adopted. According to the results, 7.3% of teeth were inadequate and there was no statistically significant difference among the groups of anterior teeth, incisors and canines (p>0.05). A ledge was present in 6.54% of root canals, a zip in 0.75% of root canals, and only one root canal presented a fractured instrument. In teeth with moderate curvature, the root curvature was a factor that possibly influenced the occurrence of ledges (p<0.05). In conclusion, the majority of root canal preparations were considered appropriate, due to the low occurrence of iatrogenesis on endodontics treatments performed by undergraduate students from Universidade Federal do Espírito Santo.